COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN TANAH HUTAN MILIK PERHUTANI KESATUAN PEMANGKU HUTAN (KPH) SUKABUMI - Revindra Al Ghivary; Mawar (Jurnal PubBis, 2023)
ABSTRACT Forest management carried out by Perhutani Sukabumi Forest Stakeholders Unit is carried out in collaboration with Forest Village Community Institutions, this is because at the beginning of forest management there were a lot of theft, illegal logging, and looting that occurred in Perhutani's forests in the collaboration that was carried out had problems namely the lack of communication and coordination, information in the field that has not been responded to properly, and the lack of work productivity and creativity that affects collaboration. The purpose of this research is to find out and analyze collaborative governance of forest land management owned by Perhutani Sukabumi Forest Stakeholders Unit. The method used in this research is a qualitative descriptive method, with research data sources coming from Perhutani KPH Sukabumi and Sukabumi Forest Village Community Institutions. Data collection techniques used were interviews, observation, and documentation, as well as data analysis techniques used were data reduction, data presentation and also drawing conclusions. The results showed that the indicators for the initial conditions of Perhutani, the Sukabumi Forest Stakeholder Unit, were quite good because with the existing conditions, Perhutani's steps to collaborate were correct and always held deliberations and socialization to reduce differences in perceptions. The implications of the research obtained are the selection of communication methods, namely deliberations and negotiations as well as steps to collaborate with Forest Village Community Institutions which are very influential for forest management. So, a conclusion can be drawn that the Collaboratove Governance that has been carried out is quite good.